FACTORS DETERMINING VULNERABILITY ON ONLINE SOCIAL NETWORKS AMONG TEENAGE GIRLS ATTENDING A CHILD DAY CARE CENTRE - Žukauskienė, Lilia; Skališienė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the results of the qualitative research which provide a deeper understanding of the factors determining vulnerability on online social networks among teenage girls attending a Child Day Care Centre. The research has involved the specialists from Child Day Care Centres of different towns and districts of Lithuania. A version of a systematic grounded theory (Strauss & Corbin, 1990) has been applied to conduct the research; it has helped to construct the phenomenon – Insight into threats on online social networks: “One step and everything can end up badly”. By applying the paradigmatic model of “cause and effect” of the systematic grounded theory, reasons for the development of this phenomenon, contextual and intervening factors, strategies of actions/interactions applied by the specialists as well as the manifested consequences have been distinguished.